Ketiadaan Pengaturan Hak Untuk Tidak Menganut Agama Atau Kepercayaan Sebagai Bentuk Ketidakselarasan Hukum Nasional dengan HAM - Mochammad Farrel Adhi Pramana; Tomy Michael (Media Hukum Indonesia (MHI), 2026)
Freedom of religion or belief constitutes a fundamental human right guaranteed by the Indonesian Constitution and various international human rights instruments. However, the Indonesian legal system has not explicitly recognized the right not to adhere to any religion or belief, raising questions regarding its compatibility with international human rights standards. This study aims to examine the regulation of the right not to profess a religion or belief within the Indonesian legal system and to assess its conformity with human rights principles following Indonesia's ratification of the International Covenant on Civil and Political Rights (ICCPR). This research employs a normative legal research method using both the statutory and conceptual approaches. Primary, secondary, and tertiary legal materials were analyzed qualitatively through systematic and comparative legal interpretation. The findings reveal that the 1945 Constitution of the Republic of Indonesia, Law Number 39 of 1999 on Human Rights, and other relevant legislation recognize the rights to profess a religion, embrace a belief, and practice religious worship, yet they do not explicitly acknowledge the right not to adhere to any religion or belief. This legal omission constitutes a normative gap that limits the scope of legal protection under national law and demonstrates its inconsistency with Article 18 of the ICCPR and General Comment No. 22, which recognize such a right as an integral element of freedom of thought, conscience, and religion. Accordingly, the study argues that harmonization of national legislation is necessary to ensure comprehensive legal protection for all dimensions of freedom of thought, conscience, religion, or belief in accordance with international human rights standards.